2020
DOI: 10.5614/ejgta.2020.8.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Alpha graphs with different pendent paths

Abstract: Graceful labelings are an effective tool to find cyclic decompositions of complete graphs and complete bipartite graphs. The strongest kind of graceful labeling, the α-labeling, is in the center of the research field of graph labelings, the existence of an α-labeling of a graph implies the existence of several, apparently non-related, other labelings for that graph. Furthermore, graphs with α-labelings can be combined to form new graphs that also admit this type of labeling. The standard way to combine these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The study of Kannan et al on the exponential mean labeling of a few different graphs studied through duplicate operations is examined for the present study [8]. Barrientos' study on alpha graphs has demonstrated the presence of α-labeling of a tree using various vertices and lengths of base path and proved that these trees can be utilized to demonstrate unicycle graphs with α-labeling [9]. Studies on cordial labeling between paths and cycles for a Cartesian product have dem-onstrated that these Cartesian products, under any conditions, are always cordial and even proved that two path Cartesian products are always cordial [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Kannan et al on the exponential mean labeling of a few different graphs studied through duplicate operations is examined for the present study [8]. Barrientos' study on alpha graphs has demonstrated the presence of α-labeling of a tree using various vertices and lengths of base path and proved that these trees can be utilized to demonstrate unicycle graphs with α-labeling [9]. Studies on cordial labeling between paths and cycles for a Cartesian product have dem-onstrated that these Cartesian products, under any conditions, are always cordial and even proved that two path Cartesian products are always cordial [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have followed Rosa' seminal work and multiple classes of α-trees are known. For example, in [9], Kotzig proved that almost all trees can be α-labeled; other two families of α-trees are the path-like trees [1] and the triangular trees [4]. Gallian [7] devotes an entire section of his survey to this labeling.…”
Section: Introductionmentioning
confidence: 99%